Uporaba sodobnih merilnih sistemov v treningu deskarjev na snegu prostega sloga - Bračič, Mitja (Šport (Ljubljana), 2013)
The development of sports training and rehabilitation are closely linked to new technological, research and organisational methods in the training process. Over the past few years, the training methods and rehabilitation are not based only on experience and intuition, but also on technologies in the training process which yield objective indicators of the athlete's or patient's preparedness. Effective training methods and rehabilitation are a product of a programmed and controlled training process. The technological equipment is available in laboratories which meet international standards for expert developmental and scientific research activities in functional diagnostics. Without information on motor, physical, physiological and biochemical characteristics it is impossible to accurately plan, programme and model the modern training process. The acquired data facilitate the process of selecting the optimal methods and means for training methods and rehabilitation as well as planning and modifying the sports preparation of an individual or a homogeneous group.
Keywords: deskanje na snegu; odrivna moč; snowboard; sport; sports diagnostics; šport; športna diagnostika; športni trening; take-off power; TMG